Responsibilities of a Substitute Notary Due to His Negligence in Making a Deed Without Applying the Precautionary Principle - Nathania Earlene Rosaria Hutabarat (Universitas Labuhanbatu, 2024)
A notary is an official who has the authority to make authentic deeds and has other authorities as mentioned in article 1 number 1 UUJNP. This authentic deed made by a notary serves as evidence. However, in practice, negligence can occur in notaries and substitute notaries in carrying out their duties, resulting in the authentic deed being made losing its validity or becoming legally void and invalid. The purpose of this research is to understand the responsibilities of notaries in making deeds. This research uses doctrinal research methods. From the research results, it can be concluded that the substitute Notary will remain responsible for every deed he or she makes if the notary's leave has ended and the protocol has been handed back to the replaced notary. Negligence in making a deed which was only discovered after some time due to a typographical error in a deed which did not comply with the wishes of the related parties caused by the notary: a If it is proven that there is no subjective element at all in the deed, then the deed can be cancelled. b. If it is proven that it does not contain objective requirements, the deed can be considered legally void. c. The notarial deed becomes invalid, so it cannot be used as perfect evidence. Keywords: Notary, responsibility, prudence